Enhancing Student Mark Management Through Web Based System - Hassan, Rosilah; Ab Rahaman, Muhammad Syahrin; Wan Mohd Ghazali, Khadijah; Md. Ali, Zulkarnain; Lim, Fang Fang (2011)
In search of technological modernization, the Internet is the main medium of delivery. Education today is seen as leading to the development of the information age. Hence the approach to education is also in line with the latest technology. The use of Information and Communication Technologies (ICT) in teaching and learning has become an important method to increase the efficiency and effectiveness of the education management process. On the other hand, the ICT is also used in education to manage student information. Management of student information especially students’ marks is a burdensome task, requiring lecturers to devote more time to complete the task within the stipulated time. Besides, the lecturers who teach more than one class and have more than one marking category such as quizzes, assignments and lab exercises find this task very complicated. The use of software such as Microsoft Excel can be helpful but cannot solve all mark management requirements due to limitation of its function. Therefore, an online students’ mark management system was developed to facilitate the process of mark calculation for the lecturers in the Faculty of Information Science and Technology. By using this system, lecturers can record each student’s marks and the system will automatically compute and issue the student’s grade. In addition, analysis will be conducted in which the system will generate reports and graphs for each subject. The system was developed using the ASP.NET web application development tool, programming language C# and JavaScript as the language support, whereas the Microsoft SQL Server is used as the database tool and ASP.NET Development Server as the web server.